(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the frequency of premature coronary bypass graft occlusions after coronary artery bypass graft surgery. Study Design: Descriptive case series study. Place and Duration of Study: This study was conducted at the department of cardiovascular medicine, Chaudhary Pervaiz Ellahi Institute of Cardiology, Multan from March to September 2018. Materials and Methods: This descriptive case series included 292 consecutive patients between one week to six months after coronary artery bypass graft surgery. The age range between 40 to 70 years and includes patients of both genders. The patients were scanned using a 128-section multi-detector computerized tomography scanner. Findings were interpreted by a consultant cardiologist. Frequency of venous and arterial graft occlusions and associated risk factors were noted. Results: Mean age of the patients was 52.60 ± 7.72 years. Out of the 292 patients, 242 (82.88%) were male and 50 (17.12%) were female. In this study, 584 were vein conduits and 292 were arterial conduits. CT coronary angiogram identified graft closure in 69 (7.88%) out of 876 total grafts. Out of total 584 vein conduits 52 (8.90%) were occluded. On the other hand, out of total 292 arterial conduits 17 (5.82%) were occluded. Conclusion: There is a substantial overall frequency of early graft occlusion including both arterial and vein conduits. In patients who underwent coronary artery bypass surgery, 7.88% had early graft occlusion.